Electrochemical oxidation of C3 saturated alcohols on Co3O4 in alkaline. (20th February 2017) - Sun, Shengnan; Sun, Libo; Xi, Shibo; Du, Yonghua; Anu Prathap, M.U.; Wang, Zilong; Zhang, Qichun; Fisher, Adrian; Xu, Zhichuan J.
Graphical abstract: Highlights: A systematic study on the electrochemical oxidation of C3 saturated alcohols on Co3O4 in alkaline. Activity trend : p ropanetriol > 1, 2 - p ropanediol > 1, 3 - propanediol > 1 - propa nol > 2 - propanol in 1.0 M KOH. The C-C bond cleavage occurred faster in alcohols having adjacent hydroxyl groups. The KOH concentration influenced electro-oxidation of those alcohols bearing secondary hydroxyl group more dramatically than that of those primary alcohols. Abstract: In this work, we present a systematic study on the electrochemical oxidation of C3 saturated alcohols (propanetriol, 1, 2-propanediol, 1, 3-propanediol, 1-propanol, and 2-propanol) on Co3 O4 in alkaline. Co3 O4 electrode was prepared by electrodeposition of Co(OH)2 on graphite paper followed with a calcination step. The electro-oxidation of C3 saturated alcohols were investigated by a combination of cyclic voltammetry, multi-step chronoamperometry, and electrochemical impedance spectroscopy techniques in KOH solution. The electro-oxidation studies at Co3 O4 electrode followed an activity trend in the following order: propanetriol (GLY) > 1, 2-propanediol (1, 2-P) > 1, 3-propanediol (1, 3-P) > 1-propanol (1-P) > 2-propanol (2-P). The NMR analysis of the oxidized products showed that C-C bond cleavage occurred faster in alcohols having adjacent hydroxyl groups. X-ray absorption near-edge structure (XANES) spectroscopy study showed that there was no significant difference in Co oxidation state in the absence and the presence of glycerol. It was also found that the KOH concentration influenced electro-oxidation of those alcohols bearing secondary hydroxyl group (GLY, 1, 2-P, and 2-P) more dramatically than that of those primary alcohols (1.3-P and 1-P).